2000
DOI: 10.1074/jbc.275.5.3313
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Residues of S-modulin Responsible for Interaction with Rhodopsin Kinase

Abstract: S-modulin in frog or its bovine homologue, recoverin, is a 23-kDa EF-hand Ca 2؉ -binding protein found in rod photoreceptors. The Ca 2؉ -bound form of S-modulin binds to rhodopsin kinase (Rk) and inhibits its activity. Through this regulation, S-modulin is thought to modulate the light sensitivity of a rod. In the present study, we tried to identify the interaction site of the Ca 2؉ -bound form of S-modulin to Rk. First, we mapped roughly the interaction regions by using partial peptides of S-modulin. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…The EF-hand domain 1, which cannot itself coordinate metal, has been shown to be crucial for GCAP-1 and GCAP-2 interaction with RetGC (18 -20, 30, 42) and in some other NCS proteins for interaction with their targets (43)(44)(45). We found a striking effect of EF-hand 2 occupation by Mg 2ϩ on the conformation of the EF-hand 1 domain, revealed by its fluorescence spectra (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…The EF-hand domain 1, which cannot itself coordinate metal, has been shown to be crucial for GCAP-1 and GCAP-2 interaction with RetGC (18 -20, 30, 42) and in some other NCS proteins for interaction with their targets (43)(44)(45). We found a striking effect of EF-hand 2 occupation by Mg 2ϩ on the conformation of the EF-hand 1 domain, revealed by its fluorescence spectra (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…A similar approach was used to understand the different capabilities of the same recoverin variants to inhibit rhodopsin kinase in a Ca 2ϩ -dependent manner. In a recent mutational study on the frog recoverin homolog S-modulin, Tachibanaki et al (43) identified seven conserved amino acid residues that were proposed to constitute an interaction surface for rhodopsin kinase. Based on the degree of preservation of Ca 2ϩ -induced conformational changes as assessed by CD spectroscopy, the authors defined "probable" (residues Phe 23 , Glu 27 , Phe 56 , and Thr 93 ) and "possible" (residues Thr 21 , Phe 57 , and Lys 101 ) interaction sites.…”
Section: Discussionmentioning
confidence: 99%
“…The kinases were affinity-purified with nonacylated S-modulin as described in ref. 22 and concentrated in the K-gluc buffer. The amount of the expressed protein was quantified with Coomassie brilliant blue staining after SDS͞PAGE, using BSA as a standard.…”
Section: Expression and Purification Of Recombinant Rod Kinase And Conementioning
confidence: 99%